Lurasidone‐Induced Tardive Syndrome. Issue 7 (24th July 2019) - Tripathi, Richa; Reich, Stephen G.; Scorr, Laura; Guardiani, Elizabeth; Factor, Stewart A.
ABSTRACT: Introduction: Tardive syndrome (TS) is an often irreversible movement disorder caused by dopamine receptor‐blocking agents (DRBAs). Although TS are well recognized to occur with typical antipsychotics, less well appreciated is that atypical antipsychotics also carry a risk of TS. Methods: Case series. Results: We describe 4 patients who developed tardive dystonia, tardive akathisia, and drug‐induced parkinsonism with the use of the atypical antipsychotic, lurasidone, which was U.S. Food and Drug Administration approved in 2013 for use in bipolar disorder and schizophrenia. Conclusion: Movement disorders are reported as a rare side effect of lurasidone, and, as such, prescribers may perceive a false sense of security regarding this potential complication. Our cases indicate that this relatively new atypical antipsychotic may cause irreversible disabling TS as well as parkinsonism. Caution must be taken when prescribing lurasidone. Abstract : View Supplementary Video 1